Committing Thoughtcrime: A Step-by-Step Tutorial (2021) - An artist from Belarus (The February Journal)
The 2020 Belarusian presidential elections provoked a severe political crisis that continues to this day. Over the past two years, Belarusians have faced unprecedented brutality from the authorities. A year after the elections, people could be arrested not only for attending protests, but also for merely showing solidarity with prisoners, for expressing any thought that differed from the official narrative. This performance, in which the author gazes silently into the camera, was an emotional reaction to the news about a student having been detained for expressing her gratitude to one of her teachers, who had been arrested.